Nomenclature of the Sphyraenidae (Teleostei: Carangaria): A synthesis of fossil- and extant-based classification systems - Ballen, Gustavo A. (Zootaxa, 2019)
A nomenclature for the family Sphyraenidae is constructed using genus-group and species-group names from both extant and extinct taxa. The Sphyraenidae is found to contain only two genera: The monotypic †Parasphyraena, and Sphyraena. “Sphyraena” amici and “Sphyraena” viennensis are retained in the genus Sphyraena pending a reassessment of their relationships. Although currently allocated out of the Sphyraenidae, the genus †Hypsodon is found to present a problematic status with respect to other fossil genera such as †Pachyrhizodus. Sphyraena intermedia Pastore is found to be a primary homonym of †Sphyraena intermedia Bassani and therefore deemed unavailable and invalid. The ambiguities of collective, otolith-based names are discussed in the context of Sphyraena hansfuchsi, the only species of the family based on otoliths. Fifty-three valid species of Sphyraena are recognized, 28 extant and 25 extinct. Comments on the usefulness of a subgeneric classification for the largest genus, Sphyraena, are made in the context of our current knowledge of their interrelationships.